The EQIPD framework for rigor in the design, conduct, analysis and documentation of animal experiments: comment - Vollert, Jan; Macleod, Malcolm; Dirnagl, Ulrich; Kas, Martien J.; Michel, Martin Christian; Potschka, Heidrun; Riedel, Gernot; Wever, Kimberley E.; Würbel, Hanno; Steckler, Thomas; Rice, Andrew S. C. (Nature methods, 2022)
The EQIPD framework for rigor in animal experiments aims to unify current recommendations based on evidence behind their rationale and was prospectively tested for feasibility in multicenter animal experiments.